Diagnostic utility of bone marrow aspiration in bicytopenia - Sandhu, Silvi; Vaid, Arundhati; Khajuria, Ruchi; Kaur, Ameet; Sharma, Ayushi (International Journal of Research in Medical Sciences, 2023)
Background: Haematological diseases are frequently seen now a days in different age groups. Patients can present with a variety of presentations in form of cytopenia of a single lineage or in a dual combination or with pancytopenia. Our study focusses on the utility of bone marrow aspiration for diagnosis of bicytopenias by assessment of pattern of bicytopenias in peripheral smear examination. Methods: This was a retrospective study that was conducted over a period of one year in a tertiary care institute of Northern India. Cases of bicytopenia were subjected to bone marrow aspiration and parameters such as cellularity, myeloid to erythroid ratio and cytomorphological details of the cells were documented. Results: Study consisted of male predominance with maximum patients in the age group of 21-30 years. Most common bicytopenia was found to be anaemia with thrombocytopenia and normoblastic erythroid hyperplasia was the most common aetiology.The results of this study were similar to those in the earlier literature with the inference that bone marrow aspiration performed for all cases significantly helped in arriving at the diagnosis. Conclusions: Bicytopenia is a good haematological indicator for many non-malignant and malignant diseases. Knowledge of its aetiologies can help in the diagnosis and efficient management of patients. Bone marrow study forms a cost-effective tool in interpretation of bicytopenia.